Tanggung Jawab Hukum terhadap Adanya Wanprestasi dalam Perjanjian Sewa Menyewa Rumah Toko (Ruko) - I Made Sukayasa; I Nyoman Putu Budiartha; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
Economic competition is a priority for business actors in various regions and cities, so that many renovation of buildings are carried out with the construction of shop-houses. The economic system is increasingly developing, so the shophouses that have been built can be used as a means of buying and selling. Shophouses are often known as shop houses or residences which are used as a place of business and usually these shophouses are built parallel to other shop buildings. This study aims to describe the certainty of the Shophouses rental agreement and explain the legal responsibility if one of the parties defaults on the implementation of the Shophouses rental agreement. This research is designed to use normative law, which is literature law which refers to the legal norms contained in statutory regulations. The statutory approach is to carry out a study based on the law as the basis for this research, while the data sources used are primary and secondary legal data. Data is obtained through legal science books without deviating from positive law in order to form a conclusion. The results showed that an agreement between the tenant and the owner of the building can create rights and obligations between the parties that are written in an agreement, this has been regulated in the Criminal Code. The lessee has the obligation to assign rights, namely the building that is leased to the tenant and has the right to get payment from the tenant for the leased building. The tenant may not transfer the rights to the building he leases and if there is a dispute in the future between the parties, it must be resolved because of default.